Potensi Jintan Hitam (Nigella sativa) sebagai Agen Antibakteri terhadap Bakteri Patogen Klinis - Allyssia Salma; Kadeq Novita Prajawanti; Bella Fevi Aristia; Khoirun Nisyak; Widji Soeratri (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Antibacterial substances such as thymoquinone, carvacrol, thymol, and p-cymene are found in black cumin (Nigella sativa), a type of herb. This study reviewed 12 recent scientific publications to assess the antibacterial efficacy of N. sativa against clinical pathogenic microorganisms. A comprehensive literature review of in vitro, in silico studies, and applications was conducted. The study found that black cumin extract and oil were more efficient against Gram-positive bacteria such as Staphylococcus aureus than Gram-negative bacteria such as Escherichia coli and Salmonella typhi. The antibacterial activity increased with the concentration of the extract, especially in the polar form (ethanol). Active compounds such as thymoquinone also showed high binding affinity to MRSA bacterial proteins molecularly. The application of N. sativa in the form of ointments, antibacterial textiles, and dental health products also showed good effectiveness. Based on these findings, Nigella sativa has great potential as a safe and environmentally friendly natural antibacterial alternative, although further clinical studies are needed to validate its efficacy and safety.